ANALISIS SAHAM-SAHAM LQ45 UNUK MEMBENTUK PORTOFOLIO YANG OPTIMAL DENGAN MENGGUNAKAN SINGLE INDEX MODEL - Zul Azhar (Universitas Pakuan, 2016)
The purpose of this research is to determine the 45 blue chip stocks which are included in the optimal portfolio with a single index models and determine the value of expected return and standard deviation of the optimal portfolio by using a single index models. The data in this study performed statistically descriptive. The conclusion of this study is to assist in investing should do anallisis with a single index models.Keywords : Investment, Investor, portofolio, risk. Single index model